What is Zero-Shot Learning in Medical Diagnosis? The AI Revolution for Rare Diseases - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The rapid advancement of Artificial Intelligence AI is transforming nearly every sector, and healthcare is no exception. AI models are increasingly adept at ...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Precision Medicine